The Effectiveness of Gallery Walk in Improving Students Writing Competence - Astri Riance; Maya Saftari; Sinta Sinta (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study was conducted to know the effectiveness of gallery Walk in improving students writing competence. The object of this study was the students at AI class Computer major Bina Insan University, amounted 32 students. This study was used Classroom Action Research Method (CAR). There were three treatment when doing this research, pre cycle, cycle I and cycle II.  From the results of observations that have been made in learning activities, it shows that there is an increase in student learning outcomes. From the results of initial or pre-cycle observations, there were only 19 students or 60.8% who completed, then it increased in the first cycle activities, namely to 27 students or 86.4%. %, so in cycle II it increased again to 30 people or 96%. From this result it can be concluded that the success of the gallery walk method in improving student learning outcomes in learning to write English texts, in this research strengthens the reason that the gallery walk method can be an Effective alternative to be applied practically in improving student learning outcomes in learning English.